Effect of ZIF-67 derivative Co3O4 on Li-rich Mn-based cathode material Li1.2Mn0.54Ni0.13Co0.13O2. Issue 24 (15th December 2021) - Huang, Zhaoyu; Feng, Wangjun; Lei, Ziru; Li, Weixue; Zhao, Wei
Abstract: The zeolitic imidazolate frameworks 67 (ZIF-67) derivative Co3 O4 composite lithium-rich manganese-based layered oxide was successfully synthesized by a simple solid-phase sintering method and systematically studied. The introduction of the derivatives does not excessively induce changes in the transition metal layered oxide structure as tested by XRD, SEM, TEM, and XPS. The electrochemical test and analysis show that the high surface area and porous structure of the ZIF-67 derivative Co3 O4 can promote the contact efficiency of the electrode and the electrolyte, thereby delaying the structural phase change which caused by the long cycle process and suppressing the voltage attenuation. In particular, a composite ratio of 10:1 samples can most effectively improve the first coulomb efficiency, cycling stability, and structural stability of lithium-rich materials. The discharge specific capacity at 0.1 C is 258.9 mAh/g, and the first coulomb efficiency is 74.93%. Especially, the discharge specific capacity at 0.5 C is 234.1 mAh/g, and the capacity retention rate is 86.28% after 100 cycles.